Virtual Reality Technologies in the Correction of Motor Disorders and Kinesiophobia in Patients with Musculoskeletal Pathology - I. V. Pogonchenkova; M. R. Makarova; D. A. Somov; N. V. Skorobogatykh; M. A. Golovkina; E. E. Popikhina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Musculoskeletal disorders, such as osteoarthritis (OA), impact approximately 250 million individuals, contributing to disabilities among those over 50 years old. OA primarily manifests as pain, leading to functional impairments, fatigue, depression, and reduced muscle strength. The condition of kinesiophobia exacerbates pain and complicates rehabilitation efforts. Therefore, a comprehensive approach is essential, comprising psychotherapeutic treatments and physical therapy to reinforce movement confidence and diminish anxiety. The aim – to assess the clinical effectiveness of the rehabilitation system, "Hardware and Software Multimedia Complex for Remotely Controlled Rehabilitation of Patients using Virtual Reality Technologies 'DEVIRTA,'" in restoring mobility in patients with the pain due to degenerative conditions and residual limb or spine injuries. Object and methods. 62 participants, averaging 63.9±9.4 years old, with 22 males and 40 females, were included and divided into two distinct groups. The first group, consisting of 34 individuals, focused on those with degenerative joint conditions of non-inflammatory origin and injury after-math. The second group comprised patients experiencing reflex musculotonic syndromes due to degenerative spinal ailments (17 individuals) and outcomes of non-complicated lumbar spine compression fractures (11 individuals). The medical rehabilitation agenda included group therapeutic exercise sessions, low-intensity magnetic therapy, magnetic laser therapy, and a motor rehabilitation program utilizing virtual reality technology DEVIRTA-DELPHI. The rehabilitation duration spanned 10 days. Results. Findings reveal that during the second phase of medical rehabilitation incorporating virtual reality, individuals with degenerative conditions and injury-induced limb and spine issues showed a reduction in pain (p < 0.05) and exhibited enhanced lumbar flexibility and faster walking speeds. There was also a notable reduction in kinesiophobia as measured by the Tampa scale (p < 0.05) and an improvement in psycho-emotional well-being (p > 0.05). Conclusion. Conducting rehabilitation using virtual reality technology proves beneficial in alleviating pain and enhancing both functional ability and emotional health in individuals with musculoskeletal disorders. Virtual reality adeptly reduces the severity of kinesiophobia and stabilizes the psycho-emotional state. The DEVIRTA system can be seamlessly integrated into rehabilitation plans for patients dealing with degenerative or injury-related limb and spine conditions.